(2.56 X 10^-6)(1.4 X 10^-7)(2.75 X 10^-4) = ______________ *
4 answers
need answer
give me the answer
you're a rude and impatient and lazy piece of work, aren't you?
(2.56 x 10^-6)(1.4 x 10^-7)(2.75 x 10^-4)
= (2.56 x 1.4 x 2.75) x 10^(-6 - 7 - 4)
now finish it off, if you can muster up the energy to actually do any of the work
(2.56 x 10^-6)(1.4 x 10^-7)(2.75 x 10^-4)
= (2.56 x 1.4 x 2.75) x 10^(-6 - 7 - 4)
now finish it off, if you can muster up the energy to actually do any of the work
2.56 ∙ 10⁻ ⁶ ∙ 1.4 ∙ 10⁻ ⁷ ∙ 2.75 ∙ 10⁻ ⁴ = 2.56 / 10 ⁶ ∙ 1.4 ∙ 10⁷ ∙ 2.75 / 10⁴ =
2.56 ∙ 1.4 ∙ 2.75 / 10⁶ ∙ 10⁷ ∙ 10⁴ = 9.856 / 10⁽ ⁶ ⁺ ⁷ ⁺ ⁴ ⁾ =
9.856 / 10¹⁷ = 9.856 ∙ 10 ⁻¹⁷
OR
2.56 ∙ 10⁻ ⁶ ∙ 1.4 ∙ 10⁻ ⁷ ∙ 2.75 ∙ 10⁻ ⁴ =
2.56 ∙ 1.4 ∙ 2.75 ∙ 10⁽ ⁻ ⁶ ⁻ ⁷ ⁻ ⁴ ⁾ = 9.856 ∙ 10 ⁻¹⁷
2.56 ∙ 1.4 ∙ 2.75 / 10⁶ ∙ 10⁷ ∙ 10⁴ = 9.856 / 10⁽ ⁶ ⁺ ⁷ ⁺ ⁴ ⁾ =
9.856 / 10¹⁷ = 9.856 ∙ 10 ⁻¹⁷
OR
2.56 ∙ 10⁻ ⁶ ∙ 1.4 ∙ 10⁻ ⁷ ∙ 2.75 ∙ 10⁻ ⁴ =
2.56 ∙ 1.4 ∙ 2.75 ∙ 10⁽ ⁻ ⁶ ⁻ ⁷ ⁻ ⁴ ⁾ = 9.856 ∙ 10 ⁻¹⁷